APPROACHES TOWARDS HOLDING ESP CLASSES IN VOCATIONAL COLLEGES AND LYCEUMS IN UZBEKISTAN - Umarova Munira Baxodirovna (Western European Studies, 2025)
English for Specific Purposes (ESP) plays a critical role in vocational colleges and lyceums in Uzbekistan, where students require language skills tailored to their professional fields. This paper explores different approaches to teaching ESP in these institutions, emphasizing curriculum development, instructional strategies, and assessment methods. Drawing on established research and methodologies, the study highlights best practices in ESP teaching, challenges faced by educators, and possible solutions. Additionally, it examines the role of digital tools, teacher training, and policy reforms in shaping the effectiveness of ESP instruction. The discussion is grounded in theoretical perspectives from Dudley-Evans & St John (2012), Cunningsworth (1995), Wallace (1998), and others to provide a comprehensive analysis of ESP implementation in Uzbekistan.
Keywords: Vocational Institutions; Academic Contexts; Task-Based Learning